Requirements and Steps Involved In Developing Learning Materials for Non-Formal Education in Nigeria - Yusuf, Murtala Akanbi; Zakari, Bala (International Journal for Educational and Vocational Studies, 2020)
One of the important roles of adult education facilitators in Nigeria is to get involved in the development of learning materials for their learners. This responsibility is better performed if they are familiar the processes involved in the development of learning. This paper contended learning materials must be need-based, reflecting local content, supporting learners’ participation, clear and accessible, logical and coherence. The paper conclude that if facilitators follow the steps involved in development of learning materials sequentially they will be able to succeed in developing relevant and useful learning materials